Constructing Post-Imperial Britain: Britishness, 'Race' and the Radical Left in the 1960s - Burkett, J. author. aut Link
VIII, 250 p.
Keywords: The end of empire shaped the way the British public saw their place in the world, society and the ethnic and racial boundaries of their nation. Focussing on some of the most controversial organisations of the 1960s, this book illuminates their central importance in constructing post-imperial Britain.